REGIONAL CHARACTERISTICS OF THE DEVELOPMENT OF THE MUSEUMS OF WORLD COUNTRIES (Spectrum Journal of Innovation, Reforms and Development, 2023)
Today, the increase in the number of scientific studies in the field of theory and practice of museum work is determined by the increase in the interest of state bodies, public and cultural organizations, and the problems of museumization, restoration, preservation and systematization of ethnic and religious heritage. The scientific works of many scientists are devoted to the study of theoretical and practical aspects of the development of museum organizations of world countries. However, until now, there has not been a detailed comprehensive geographical analysis of the specific aspects of the development of the world's museum organizations on separate continents, countries and regions. The scope of these issues is studied in this article.